Governmental Responses to Terrorism in Autocracies: Evidence from China. Issue 1 (25th January 2022) - Potter, Philip B. K.; Wang, Chen
Abstract: Autocracies are widely assumed to have a counterterrorism advantage because they can censor media and are insulated from public opinion, thereby depriving terrorists of both their audience and political leverage. However, institutionalized autocracies such as China draw legitimacy from public approval and feature partially free media environments, meaning that their information strategies must be much more sophisticated than simple censorship. To better understand the strategic considerations that govern decisions about transparency in this context, this article explores the Chinese Communist Party's (CCP) treatment of domestic terrorist incidents in the official party mouthpiece – the People's Daily. Drawing on original, comprehensive datasets of all known Uyghur terrorist violence in China and the official coverage of that violence, the findings demonstrate that the CCP promptly acknowledges terrorist violence only when both domestic and international conditions are favorable. The authors attribute this pattern to the entrenched prioritization of short-term social stability over longer-term legitimacy.